World malaria report 2009
The 2009 "World Malaria Report" summarizes information received from 108 malaria endemic countries and other sources and updates the analysis presented in the 2008 report. It highlights progress made in meeting the World Health Assembly targets for malaria to be achieved by 2010 and 2015, and new goals on malaria elimination contained in the Global Malaria Action Plan.Readers of this Report will want to know, in comparison to last year: have finances continued to grow, to enable scale up throughout Africa and globally? Have the commodities distributed by national governments ended up in households, benefitting children, women and other adults? Is the financing and the coverage by interventions having an effect? This report provides data for two additional years, 2007 and 2008. It describes the status of malaria control both outside as well as inside Africa. In addition, it describes the full chain, from financing and policies to number of commodities distributed, intervention coverage in households and, finally, impact.Profiles of 31 countries are presented. Two or three countries with the highest malaria burden were chosen from five of the six WHO Regions. The other profiles are those of the 20 countries with the highest burden in the African Region. Following the profiles, annexes give data by country for malaria-related indicators.au